The Effect of Ownership Structure and Profitability on the Dividend Policy of Manufacturing Companies Listed on the Indonesian Stock Exchange between 2020 and 2024 - Desmizar Desmizar (Baca Dulu Publisher, 2025)
This study aims to determine the effect of ownership structure and profitability on dividend policy of manufacturing companies listed on the Stock Exchange 2020-2024. The ownership structure is measured by institutional ownership and managerial ownership, profitability measured by return on assets (ROA) and net profit margin (NPM), and dividend policy measured by dividend payout ratio (DPR). The population in this study is 133 companies manufacturing companies listed on the BEI 2020-2024. Using purposive sampling method obtained 11 companies that meet the criteria of sampling. Data analysis using descriptive statistics, normality test, multiple regression analysis and hypothesis testing. The error rate or significance used is 5%. T test results show that managerial ownership and NPM are negatively affected on dividend policy, ROA has a positive effect on dividend policy, while institutional ownership have no effect on dividend policy.